Demystifying the genius of entrepreneurship: How design cognition can help create the next generation of entrepreneurs - GARBUIO, Massimo (Institutional Knowledge at Singapore Management University, 2018)
Entrepreneurship education is a key beneficiary of design thinking’s recent momentum. Both designers and entrepreneurs create opportunities for innovation in products, services, processes, and business models. More specifically, both design thinking and entrepreneurship education encourage individuals to look at the world with fresh eyes, create hypotheses to explain their surroundings and desired futures, and adopt cognitive acts to reduce the psychological uncertainty associated with ambiguous situations. In this article, we illustrate how we train students to apply four well-established cognitive acts from the design cognition research paradigm—framing, analogical reasoning, abductive reasoning, and mental simulation—to opportunity creation. Our pedagogical approach is based on scholarship in design cognition that emphasizes creating preferred situations from existing ones rather than applying a defined set of tools from management scholarship. In doing so, we provide avenues for further development of entrepreneurship education, particularly the integration of design cognition.